A Comparative Study of The Indonesian and English Articles - FX. Nadar (Humaniora, 1996)
Commonwealth Department of Education in Australia (1983:22) has concluded that articles will be an area of difficulty for Indonesian students. This is because the" BI (Bahasa Indonesia) has no real equivalents of the English definite and indefinite articles. In many cases where the articles are used in English no corresponding word occurs in Bahasa Indonesia". Errors related to the use of articles deserve close attention because articles are not only one of the grammar elements, but also "extremely frequent in English" (Berry,1991:252). Carrol, et al (1971) have found that articles account for almost every tenth word In English. This paper means to explore the similarities and differences of the articles in Indonesian and English, and how the findings may affect Indonesian students' difficulties in using the English articles.